Assessing the Entrepreneurial Readiness of Islamic School Students in South Sulawesi for Participation in the Global Halal Economy? - Alam, Ade Ikhlas Amal; Fauzan Garantjang, Muhammad; Anissa Aulya Putri .T; Rispan, Dhiya Pravidya (Amkop Management Accounting Review (AMAR), 2025)
This study aims to assess the readiness of Islamic school students in South Sulawesi in halal-based entrepreneurship and identify the obstacles they face in meeting halal certification standards. With the growing halal industry in Indonesia and the increasing demand for halal-certified products, sharia-based entrepreneurship education is important to form a competitive young generation in this sector. However, there are still limitations in students' understanding of halal regulations, certification procedures, and business management in accordance with sharia principles. Therefore, this study examines the extent to which Islamic education programs have prepared students to become professional and competitive halal entrepreneurs. This research is closely related to Sustainable Development Goal 8 (SDG 8) - Decent Work and Economic Growth, as it focuses on creating economic opportunities for youth through halal entrepreneurship. By equipping students with a deeper understanding of halal standards and the Islamic financial system, it is hoped that they will be able to establish their own businesses and contribute to more inclusive economic growth. In addition, this research also aims to provide concrete recommendations for educational institutions and the government in improving education and socialization regarding the halal industry, so as to strengthen the halal MSME ecosystem in Indonesia and encourage the competitiveness of young business actors at the global level